Person-Job Fit As a Dominant Factor That Directly Improves Employee Performance: Study At PT PLN (Persero) Semarang City - Siska Dwi Nuryanti; Sih Darmi Astuti; Agus Prayitno; Mila Sartika (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the influence of learning organization, person-job fit on employee performance with job satisfaction as a mediating variable. This research is through a quantitative approach, with a survey method using questionnaires as a data collection technique. The method used in sampling is purposive sampling with the criteria in sample selection being employees with a minimum working period of 3 years as many as 97 respondents. The results of the study found that 1) Learning Organization does not have a direct impact on the performance of employees of PT PLN (Persero) Semarang City, 2) Person-Job Fit has a significant influence on the performance of employees of PT PLN (Persero) Semarang City, so the more aligned the work with the employee's skills, the greater their productivity. 3) Job satisfaction plays a mediator in the relationship between the Learning Organization and Person-Job Fit to employee performance.